Dragon Mimic Shape Facilitate Ultrahigh‐Performance Flexible All‐Perovskite Tandem Solar Cells. Issue 7 (12th February 2023) - Wang, Weijian; Yu, Gang; Attique, Sanam
Abstract : Flexible tandem solar cells (FTSCs) are a kind of photovoltaic device with enormous potential application value that truly integrates low cost and high efficiency. Perovskite materials have immediately become a dazzling new star in the field of tandem solar cells and flexible solar cells (FSCs) owing to their groundbreaking optoelectronic properties. However, compared with rigid solar cells, the photoelectric conversion efficiency of FSCs still has considerable room for improvement, which is mainly limited by the optical loss of the device. Herein, inspired by the shape of the Chinese dragon, various types of two‐terminal (2T) all‐perovskite FTSCs are constructed utilizing bionic concepts and the finite‐element method and wave optics theory are coupled to study the device's performance. The optical performance of flexible photovoltaic devices is influenced by structure size parameters. In addition, the dependence of the 2T all‐perovskite FTSCs on the light incident angle is also investigated. Finally, the total photocurrent ( J ph ) value of the device reaches 37.63 mA cm −2 ( J top  = 18.82 mA cm −2, J bottom  = 18.81 mA cm −2 ). The optical properties of all‐perovskite FTSCs are demonstrated in the simulation results with ultralow surface reflection and it is found extremely insensitive to the incident angle of light. The designed 2T all‐perovskite FTSCs provide a practical route to realize high‐efficiency, low‐cost photovoltaic modules. Abstract : Inspired by the traditional Chinese dragon shape, a flexible tandem perovskite solar cell with a theoretical photoelectric conversion efficiency of 34.83% is designed for the first time using the bionic concept and simulation method combined with the finite‐element method and wave optics theory. Herein, a practical way is presented to design high‐performance flexible tandem photovoltaic devices.